SIV infection induces alterations in gene expression and loss of interneurons in Rhesus Macaque frontal cortex during early systemic infection - Richard C. Crist; Samar N. Chehimi; Saurabh S. Divakaran; Michael J. Montague; Sébastien Tremblay; Noah Snyder-Mackler; Martin O. Bohlen; Kenneth L. Chiou; Trish M. Zintel; Cayo Biobank Research Unit; Michael L. Platt; Halvor Juul; et al. (Translational Psychiatry)
Abstract Understanding the neurobiological mechanisms underlying HIV-associated neurocognitive decline in people living with HIV is frequently complicated by an inability to analyze changes across the course of the infection and frequent presence of comorbid psychiatric and substance use disorders. Preclinical non-human primate simian immunodeficiency virus (SIV) models help address these shortcomings. However, SIV studies frequently target protracted endpoints, limiting our understanding of the neuromolecular alterations during the early post-infection window. To begin to address this knowledge gap, we utilized single nuclei transcriptomics to examine frontal cortex samples of rhesus macaques 10- and 20-days post-SIV infection, compared to non-infected controls. We identify and validated a decrease in inhibitory neurons during the early post infection window, representing a potential substrate of longer-term injury and neurocognitive impairment in people living with HIV. Differential expression identified alterations in cellular subtype gene expression that persisted over the 20-day time course and short-lived differences only detected at 10-days post-SIV infection. In silico predicted regulatory mechanisms and dysregulated neural signaling pathways are presented. Analysis of cell-cell interaction networks identify altered signal pathways in the frontal cortex that may represent regional alterations in cell-cell communications. In total, these results identify cell type-specific molecular mechanisms putatively capable of underlying long-term neurocognitive alterations in persons living with HIV.